SOSIALISASI MODEL KREATIVITAS PERMAINAN DALAM PEMBELAJARAN LARI BAGI SISWA SEKOLAH DASAR - Sinlaeloe, Andry; Palinata, Yahya Jecson; Baun, Alventur; Selan, Melvianus; Lika, James Klemen (LPPM Institut Pendidikan Nusantara Global, 2023)
Learning physical education sports and health in schools should emphasise providing direct learning experiences to achieve good skills in improving learning completeness, students can gain a variety of experiences to reveal personal impressions that are fun, creative, innovative, and skilled which are planned, implemented and evaluated systematically in order to achieve learning objectives effectively and efficiently. The method of implementing service activities includes: the preparation stage, the socialisation stage and the implementation stage. Data collected using observation sheets for running with the game model that has been prepared. The results of the implementation of the zig-zag running model carried out by GMIT Bolok Elementary School students obtained 62.5% (15 people) with Excellent criteria and 37.5% (9 people) with Good criteria, the implementation of the cone jumping and zig-zag cone jumping models obtained 100% (24 people) with Excellent criteria in accordance with normative reference guidelines. This shows that the socialisation of the game creativity model in running learning for elementary school students has succeeded in achieving learning objectives.